The Influence Of Firm Size, Leverage, Profitability And Manajerial Ownership On Earnings Management In Consumer Goods Industry Companies Listed On The Indonesia Stock Exchange - Widya Nizrina; Sucipto, Tia Novira (Universitas Dehasen Bengkulu, 2025)
This study aims to determine the effect of firm size, leverage, profitability and manajerial ownership on earnings management in consumer goods industry companies listed on the Indonesia Stock Exchange. This research is a quantitative research. The sampling method was carried out using a purposive sampling technique. This study uses secondary data, namely from the financial reports of consumer goods industry companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The sample used in this study was 102 company data, with 30 outlier company data, so that the total sample used was 72 company data. The data analysis used was multiple linear regression analysis using the SPSS Version 31 program. Based on the results of the data processing it can be concluded that firm size, leverage, profitability and manajerial ownership simultaneously doens’t have a significant effect on Earnings Management in consumer goods industry companies listed on the Indonesia Stock Exchange for the 2021-2013 period.